Perilaku Prososial dalam Masyarakat Multikultural: Tinjauan Psikologi Sosial - Sari, Fanya Puspita; Neviyarni, Neviyarni (TSAQOFAH, 2026)
Multicultural society is a social reality characterized by cultural, ethnic, religious, and social value diversity, which has the potential to become both a source of strength and a source of conflict if not properly managed. In this context, prosocial behavior plays an important role in building harmonious social relations and strengthening social cohesion between groups. This study aimed to examine prosocial behavior in multicultural society from a social psychology perspective using a literature review approach. A qualitative method was employed by analyzing and synthesizing various national and international scholarly articles relevant to prosocial behavior, empathy, social identity, social norms, cultural values, and intergroup contact. The findings show that prosocial behavior in multicultural societies is influenced by the complex interaction of empathy, social identity, social norms, cultural values, and the intensity of intergroup contact. Empathy functions as a primary psychological mechanism that motivates individuals to help and cooperate across group boundaries, while inclusive social identity expands prosocial behavior from the in-group to the out-group. In addition, positive intergroup contact and multicultural norms that support tolerance and social justice have been shown to reduce prejudice and increase prosocial behavior. This review emphasizes that strengthening empathy, inclusive values, and multicultural education constitutes a key strategy for building harmony and social cohesion amid societal diversity.